A punição afeta o policial militar quanto ao cometimento de novas infrações? - Cavalcante, Públio Pastrolin (2024)
This work presents a study on punishments received by PMDF military police officers and how this affects the commission of new disciplinary transgressions or the commission of crimes. We use a unique and confidential PMDF database that contains information about punishments received by each police officer over time from 2014 to 2022. As we have identified information about the police officer over time, we use a panel econometric model to study whether the effect of punishing generates a disciplinary effect on police officers, that is, if the probability of committing a new offense is subsequently reduced to punishment. The present study is considered unprecedented and contributes to academia as it covers an area little explored in academia, which is the study of the behavior of military police officers in the Federal District through statistical data and econometric concepts.